Interrogating Whiteness in Community Research and Action. Issue 3 (8th October 2020) - Coleman, Brett Russell; Collins, Charles R.; Bonam, Courtney M.
Abstract: Community psychology is expressly concerned with social justice. Such concern necessitates attention to race. Yet, nearly absent from the field's literature is explicit and critical attention to whiteness. Thus, community psychology's contribution to promoting social justice remains incomplete. In this article, we examine how a critical construction of whiteness can be useful for community research and action. After a brief history of the construction of whiteness in the United States, and a summary of key insights from critical whiteness studies, we present a scoping review of the nascent body of community psychology literature that addresses whiteness. That work implicates whiteness in the emergence of the field itself, frames whiteness as social location, problematizes whiteness, addresses White supremacy and institutional racism, interrogates White privilege, and employs whiteness as a theoretical standpoint. We conclude with three propositions for scholars to broker the relationship between community psychology and critical whiteness studies: (a) community psychology should become more critically conscious of whiteness, (b) community psychologists should promote critical awareness of the ways that whiteness operates as a complex system, and (c) greater critical awareness of whiteness should be applied to the development of multilevel interventions aimed at dismantling whiteness as a system of domination. Highlights: Critical evaluation of whiteness is virtually absent from community psychology literature. Other fields provide more comprehensive frameworks for interrogating whiteness. Incorporating whiteness into liberation frameworks would advance the study of social justice.